Fabrication of glass-ceramics containing nano-sized lithium niobate crystals - Prapitpongwanich P. (2014)
The glass-ceramics from (95-x)LiNbO3-xSiO2-5Al 2O3 system where 15≤x≤55 were fabricated by the incorporation method. This method requires the calcination process of the LiNbO3 powder before mixing with theglass formers which in this case are xSiO3-5Al2O3 oxides with various x values corresponding to the above formula. The as-quenched samples, of all composition under study, were confirmed to be amorphous, partly or fully crystalline solids by X-ray powder diffraction (XRD). The crystal phase obtained in most of the samples is LiNbO3 with various sizes and shapes. Microstructures and chemical compositions of the selected glass samples were studied by scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) techniques. Glass-ceramics embedded with rhombohedral lithium niobate (LiNbO3) nano-crystals were produced by the asquenched glasses at the melting temperature ranging from 1300-1400 °C with 1 h. dwell time. The dielectric properties of the glass-ceramics were also examined. © 2009 American Institute of Physics.